Adult Case of Pontocerebellar Hypoplasia without the Claustrum - Koji Hayashi; Shiho Mitsuhashi; Ei Kawahara; Asuka Suzuki; Yuka Nakaya; Mamiko Sato; Yasutaka Kobayashi (MDPI AG, 2024)
We describe the case of a 63-year-old man with pontocerebellar hypoplasia without the claustrum (CL). The patient had a history of cerebral palsy, intelligent disability, cerebellar atrophy, and seizures since birth. At age 61, brain computed tomography (CT) revealed significant cerebellar and brainstem atrophy. At age 63, he was admitted to our hospital for aspiration pneumonia. Although he was treated with medications, including antibiotics, he died one month after admission. The autopsy revealed a total brain weight of 815 g, with the small-sized frontal lobe, cerebellum, and pons. The cross-section of the fourth ventricle had a slit-like appearance, rather than the typical diamond shape. In addition, bilateral CLs were not observed. Apart from CL, no other missing brain tissue or cells could be identified. Microscopic examinations disclosed neurofibrillary tangles in the hippocampus but not in the cortex; however, neither senile plaques nor Lewy bodies were detected. No acquired lesions, including cerebral infarction, hemorrhage, or necrosis, were noted. We pathologically diagnosed the patient with pontocerebellar hypoplasia without CL. As there have been no prior reports of pontocerebellar hypoplasia lacking CL in adults, this case may represent a new subtype. Congenital CL deficiency is likely associated with abnormalities in brain development. CL may play a role in seizure activity, and the loss of bilateral CLs does not necessarily result in immediate death. Further studies are needed to clarify the functions of CL.